Serious game as oral histology learning strategy for undergraduate dental students; crossover randomized controlled trial - Lisa R. Amir; Irene C. Leonardy; Salsabila N. Dewatmoko; Rezon Yanuar; Dewi F. Suniarti; Erik Idrus; Kawin Sipiyaruk; Ria Puspitawati (BMC, 2023)
Abstract Background Oral histology is perceived by dental students as a challenging subject and often struggle to recognize the long-term relevance of understanding the cells and tissues at the microscopic level. Serious games have been reported to have a positive effect on student cognitive skills and learning motivation. However, there is still a limited amount of research supporting the effectiveness of serious games as a learning method in dentistry. The present study aimed to evaluate the impact of serious game of HistoRM as a complementary learning strategy for oral histology. Methods The study design was a crossover randomized controlled trial. A total of 74 first year dental students of Universitas Indonesia participated in the study and divided into 2 groups. Study intervention included HistoRM game for 3 days followed by a combination of HistoRM and script-based handouts for another 4 days. The groups represented different intervention sequences. Evaluation was performed using pre-test, post-test on day 3 and 7 and a questionnaire. Results The data showed significant improvement of student cognitive skills (p < 0.001) and it was influenced by the number of game missions completed. Students who completed the whole 15 missions have a higher day-7 post-tests scores (p = 0.03). Perception of dental students on HistoRM was positive in all domains tested, the learning content, games and learning experience domains. Immediate feedback given after each gameplay helped the students understand the subject matters. Conclusion Serious game of HistoRM effectively improved students' understanding of oral histology learning outcome and provided more interesting learning experiences. This innovative learning can be recommended as a complementary learning strategy of oral histology for dental students.